"Artysta największy". Eliza Orzeszkowa o Sienkiewiczu = "The greatest artist". Eliza Orzeszkowa about Sienkiewicz - Sikora, Ireneusz (1952-2016) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article aims to reconstruct - on the basis of Eliza Orzeszkowa's letters - the relationship between the authoress and Henryk Sienkiewicz. Information about his artistic and personal biography as well as his works appears in Orzeszkowa's epistolography since 1877, and returns until March 1909. Several years' period of admiring Sienkiewicz's works by Orzeszkowa and a distance on his part ended in 1880 as a result of the fact that Sienkiewicz questioned Orzeszkowa's Vilnius editorial works.
Keywords: Orzeszkowa, Eliza (1841-1910); Sienkiewicz, Henryk (1846-1916); epistolografia - 19 w.; epistolography